ANALISIS TATA KELOLA SISTEM KEUANGAN DI INDONESIA: SEBUAH PERSPEKTIF HISTORIS - Nasution, Lokot Zein (Journal of Innovation in Business and Economics, 2015)
This study aims to analyze the governance of the financial system in Indone-sia. This study uses descriptive analysis by reviewing the literature and analysis of secondary data obtained from the Ministry of Finance, Bank In-donesia (BI), the Central Statistics Agency (BPS). The results of the analysis of this study showed that based on historical experience, to mini-mize inter-nal and external obstacles have to do with governance through improved in-vestment and productive credit. This governance is done by way of coordina-tion between the actors of the financial system, the community, financiers, and government. This model is expected to be a proliferation of governance oriented to minimize the risk of the financial system in the future.Keywords: Economic Growth, Financial System History, Governance Financial System, Risk Financial System